Terapi Spiritual Doa Tafakur terhadap Peningkatan Kesejahteraan Pasien Kanker: A Systematic Review : Spiritual Therapy of Tafakur Prayer to Increase the Well-Being of Cancer Patients: A Systematic Review - Priyanto; Achmad Fauzi Kamal; Debie Dahlia; Besral Besral (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
Medical surgical nursing care is the main source of service in an effort to achieve quality improvement in the well-being of cancer patients in hospitals. The well-being of cancer patients can be improved through various nursing interventions, including spiritual therapy of tafakur prayer. This research is to synthesize the study of spiritual therapy of tafakur prayer on improving the well-being of cancer patients. This study uses a systematic review approach with quantitative methods using the PRISMA model. The dependent variable is the patient's well-being, and spiritual therapy of tafakur prayer is the independent variable. Of the 323 selected articles, 6 articles met the selected inclusion and exclusion criteria. The articles were collected from 4 database sources namely: EBSCO host, proQuest, Science Direct and Google Scholar. The results of the research show that spiritual therapy of tafakur prayer can improve the quality of life and increase physical well-being, including reducing pain and blood pressure and improving respiratory rate. In addition, spiritual therapy of tafakur prayer can improve psychological and emotional well-being including stress and anxiety as well as spiritual well-being so that it can improve the social well-being of cancer patients. Spiritual therapy of tafakur prayer can be applied by nurses in medical surgical nursing services for cancer patients in hospitals. ABSTRAK Asuhan keperawatan medikal bedah menjadi sumber utama pelayanan dalam upaya mencapai kualitas peningkatan kesejahteraan pasien kanker di rumah sakit. Kesejahteraan pasien kanker dapat ditingkatkan melalui berbagai intervensi keperawatan, termasuk terapi spiritual doa tafakur. Penelitian ini untuk mensintesis kajian terapi spiritual doa tafakur terhadap peningkatan kesejahteraan pasien kanker. Penelitian ini menggunakan pendekatan systematic review dengan metode kuantitatif menggunakan model PRISMA. Variabel dependen adalah kesejahteraan pasien, dan terapi spiritual doa tafakur sebagai variabel independen. Dari 323 artikel terseleksi ada 6 artikel yang memenuhi kriteria inklusi dan eksklusi yang dipilih. Artikel-artikel tersebut dikumpulkan dari 4 sumber basis data yaitu: EBSCO host, ProQuest, Science Direct dan Google Scholar. Hasil penelitian menunjukkan bahwa terapi spiritual doa tafakur dapat memperbaiki kualitas hidup dan meningkatkan kesejahteraan fisik, termasuk menurunkan nyeri dan tekanan darah serta memperbaiki laju pernapasan. Selain itu terapi spiritual doa tafakur dapat meningkatkan kesejahteraan psikologis dan emosional termasuk stres dan kecemasan serta kesejahteraan spiritual hingga dapat meningkatkan kesejahteraan sosial pasien kanker. Terapi spiritual doa tafakur dapat diterapkan oleh perawat dalam pelayanan keperawatan medikal bedah pada pasien kanker di rumah sakit.